1997
DOI: 10.1046/j.1365-3040.1997.d01-140.x
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric CO2 enrichment increases growth and photosynthesis of Pinus taeda: a 4 year experiment in the field

Abstract: Forest trees are major components of the terrestrial biome and their response to rising atmospheric CO2 plays a prominent role in the global carbon cycle. In this study, loblolly pine seedlings were planted in the field in recently disturbed soil of high fertility, and CO2 partial pressures were maintained at ambient CO2 (Amb) and elevated CO2 (Amb + 30 Pa) for 4 years. The objective of the study was to measure seasonal and long-term responses in growth and photosynthesis of loblolly pine exposed to elevated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

29
173
3
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(209 citation statements)
references
References 72 publications
29
173
3
3
Order By: Relevance
“…Mousseau 1993;Tissue et al 1993Tissue et al , 1999Lewis et al 1996;Tissue, Thomas & Strain 1997, Rey & Jarvis 1998Spunda et al 1998;Turnbull et al 1998; also see review by Medlyn et al 1999). For example, A max did not differ for new Q. ilex leaves but was downregulated for 1-year-old leaves at the Laiatico CO 2 spring compared to a control site (C. Cario et al unpublished results).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Mousseau 1993;Tissue et al 1993Tissue et al , 1999Lewis et al 1996;Tissue, Thomas & Strain 1997, Rey & Jarvis 1998Spunda et al 1998;Turnbull et al 1998; also see review by Medlyn et al 1999). For example, A max did not differ for new Q. ilex leaves but was downregulated for 1-year-old leaves at the Laiatico CO 2 spring compared to a control site (C. Cario et al unpublished results).…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, many other studies have reported no change or an increase in leaf area index with elevated [CO 2 ] (e.g. Tissue et al 1997; also see reviews by Saxe et al 1998 andNorby et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In most trees, net photosynthesis was stimulated 40-80% by growth in elevated CO,, with the lowest stimulation for non-shade grown trees being 20% in Mangifera indica (Goodfellow et al 1997). In loblolly pine (Pinus taeda), net photosynthesis of trees grown in the field in conditions that did not limit rooting volume was also stimulated by growth in elevated CO, (Ellsworth et al 1995, Liu and Teskey 1995, Teskey 1995, Lewis et al 1996, even after four years of CO1exposure (Tissue et al 1997). In general, net photosynthesis is enhanced in trees grown in elevated CO1 and that enhancement is maintained for long periods.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonal effects have been shown to influence the photosynthetic response to elevated COZ (El Kohen and Mousseau 1994, Curtis et al, 1995Lewis et al 1996, Tissue et al 1997, Rey and Jarvis 1998. In two deciduous trees, C'astanea sativa (El Kohen and Mousseau 1994) and Betula pendzda (Rey and Jarvis 1998), photosynthetic adjustment to elevated C02 increased as the growing season progressed.…”
Section: Discussionmentioning
confidence: 99%
“…The increased concentration of atmospheric CO 2 could enhance photosynthesis, since the uptake of CO 2 will become easier (Tissue et al 1997, Kirschbaum 2011. This might lead to a reduced ne e d f o r w a t e r. A s a re s u l t o f w a rm e r a n d l o ng e r g ro w i ng s e a s o ns , t he a m o u nt o f assimilated CO 2 could increase.…”
Section: Introduction Climate Change and Its Effect On The Carbon Cyclementioning
confidence: 99%